Loading performance of fish and OMNI-Max anchors in crust-over-soft clays. (October 2019) - Kim, Y.H.; Hossain, M.S.; Lee, J.K.
Abstract: This paper reports the results from three-dimensional dynamic finite element analysis undertaken to provide insight into the behaviour of the fish and OMNI-max dynamically installed anchors during loading in crust-over-soft clay sediments. Particular attention was focused on the situations where the anchor is embedded to a shallow depth during dynamic installation due to the strong crust layer. Large deformation finite element analyses were carried out using the coupled Eulerian-Lagrangian approach, incoporating the anchor chain effect. Parametric analyses were undertaken varying the initial embedment depth, anchor shape, loading angle, strength ratio between the top and bottom layers. The tracked anchor trajectory confirmed that the diving potential of the fish and OMNI-Max anchors were enhanced by the presence of the crust layer as that somewhat restircted the upward movement. This will be beneficial for many hydrocarbon active regions with layered seabed sediments where the anchor embedment depths during dynamic installation are expected to be low.